Effect of glycosides based standardized fenugreek seed extract in bleomycin-induced pulmonary fibrosis in rats: Decisive role of Bax, Nrf2, NF-κB, Muc5ac, TNF-α and IL-1β. (25th July 2015) - Kandhare, Amit D.; Bodhankar, Subhash L.; Mohan, Vishwaraman; Thakurdesai, Prasad A.
Graphical abstract: Highlights: SFSE-G enhanced BALF and lung antioxidant (SOD, GSH, T-AOC, MDA, NO, Nrf2) status. Lung inflammatory markers (TNF-α, IL-1β, IL-6 and IL-8) down-regulated by SFSE-G. It down-regulates fibrotic (TGF-β, collagen-1, ET-1, Muc5ac, NF-κB, Smad-3) markers. Lung histological and ultrastructural aberration was reduced by SFSE-G. SFSE-G has potential anti-fibrotic efficacy to prevent BLM induced PF. Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive multifactorial disease with limited therapeutic options. Glycosides based standardized fenugreek seed extract (SFSE-G) possesses potent anti-inflammatory and anti-oxidant property. Aim: To evaluate the efficacy of SFSE-G against bleomycin (BLM) induced pulmonary fibrosis by assessing behavioral, biochemical, molecular and ultrastructural changes in the laboratory rats. Materials and methods: IPF was induced in male Sprague-Dawley rats by single intratracheal BLM (6 IU/kg) injection followed by SFSE-G (5, 10, 20 and 40 mg/kg, p.o.) or methylprednisolone (10 mg/kg, p.o.) treatment for 28 day. Various parameters were analyzed in lung and bronchoalveolar lavage fluid (BALF) after 14 and 28 days of the drug treatment. Results: SFSE-G (20 and 40 mg/kg, p.o.) administration significantly prevented the BLM induced alteration in body weight, lung index, lung function test and hematology. The altered total and differential cell count in BALF and blood was significantly prevented by SFSE-G treatment. The decreased peripheral blood oxygen content after BLM instillation was significantly increased by SFSE-G treatment. SFSE-G significantly enhanced the BALF and lung antioxidant status, through modulating the SOD, GSH, T-AOC, MDA, NO level and Nrf2, HO-1 mRNA expression. There was a significant reduction in lung 5-HT level by SFSE-G treatment. The altered mRNA expression of biomarkers of lung inflammation (TNF-α, IL-1β, IL-6 and IL-8), fibrosis (TGF-β, collagen-1, ET-1, Muc5ac, NF-κB, VEGF, Smad-3) and apoptosis (Bax, Bcl-2 and Caspase-3) were significantly prevented by SFSE-G treatment. BLM induced histological inflammatory and fibrotic insult in the lung were reduced by SFSE-G treatment. It also ameliorated BLM induced lung ultrastructural changes as observed by transmission electron microscopic studies. However, administration of SFSE-G (5 mg/kg, p.o.) failed to show any protective effect against BLM-induced PF whereas SFSE-G (10 mg/kg, p.o.) showed significant amelioration in BLM-induced PF except lung function test, BALF and lung antioxidant level. Conclusion: SFSE-G showed anti-fibrotic efficacy executed through induction of Nrf2, which in turn may modulate anti-inflammatory molecules, inhibit fibrogenic molecules and decreased apoptosis to ameliorate BLM induced pulmonary fibrosis.